Improving the energy efficiency of two-speed motors through the use of new pole-switched windings - Zhanat Issabekov; Dauletbek Rismukhamedov; Khusniddin Shamsutdinov; Shakhobiddin Husanov; Sabit Rismukhamedov; Bibigul Issabekova; Assemgul Zhantlessova (Institute of Advanced Engineering and Science, 2026)
This article addresses the design and manufacturing of two-speed asynchronous motors with pole-changing windings. The need for developing two-speed motors with a single pole-changing winding is justified from the standpoint of energy and resource efficiency, as well as improved starting performance of high-power electric drives. An analysis of existing pole-changing winding designs is presented, highlighting their practical limitations in industrial applications. A new pole-changing winding with a 4/2 pole ratio and 48 stator slots was developed using the discrete spatial functions method based on star–delta–double star configurations. The electromagnetic characteristics of the proposed winding were analyzed. Based on this design, a new 4A200L8/4U3 two-speed motor was manufactured and tested under production conditions at the energy motors plant. Experimental results show that at p1 = 4 pole pairs the motor delivers P2 = 20 kW with efficiency η = 87%, cos φ = 0.82, I1 = 43 A at slip s = 2.35%, while at p2 = 2 pole pairs it develops P2 = 36 kW with efficiency η = 91.5%, cos φ = 0.906, I1 = 66 A at slip s = 1.5%. The results confirm more efficient utilization of the active magnetic core at lower polarity and demonstrate the feasibility of implementing such motors for energy-saving applications in heavy-duty drives requiring two equivalent operating speeds.